2017
DOI: 10.1074/jbc.m117.783845
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 promotes Hedgehog signaling through a novel cytoplasmic motif

Abstract: Hedgehog (HH) signaling critically regulates embryonic and postnatal development as well as adult tissue homeostasis, and its perturbation can lead to developmental disorders, birth defects, and cancers. Neuropilins (NRPs), which have well-defined roles in Semaphorin and VEGF signaling, positively regulate HH pathway function, although their mechanism of action in HH signaling remains unclear. Here, using luciferase-based reporter assays, we provide evidence that NRP1 regulates HH signaling specifically at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 90 publications
3
37
0
Order By: Relevance
“…DRG neurons have been widely used to decipher molecular mechanisms of axonal outgrowth, axon guidance, and branching in vitro [ 56 , 57 , 58 ]. Interestingly, some of the major guidance receptors, such as Robo1 and Neuropilin-1, have recently been localized to the primary cilium of neurons in the CNS and mouse fibroblasts, respectively [ 43 , 59 ]. Hence, it is possible that some of the signaling pathways involved in axonal development might be transduced at the primary cilium level.…”
Section: Discussionmentioning
confidence: 99%
“…DRG neurons have been widely used to decipher molecular mechanisms of axonal outgrowth, axon guidance, and branching in vitro [ 56 , 57 , 58 ]. Interestingly, some of the major guidance receptors, such as Robo1 and Neuropilin-1, have recently been localized to the primary cilium of neurons in the CNS and mouse fibroblasts, respectively [ 43 , 59 ]. Hence, it is possible that some of the signaling pathways involved in axonal development might be transduced at the primary cilium level.…”
Section: Discussionmentioning
confidence: 99%
“…Before presenting those evidences, we should give some information about hedgehog (HH) signaling. Briefly, HH signaling is essential for tissue patterning and organ formation during embryonic and postnatal development, as well as in cancer development and tissue homeostasis renewal and repair in adult animals [68]. The HH pathway acts via activation of transcriptional effectors, such as the glioblastoma (Gli) proteins, a family of transcription factors whose target genes remain enigmatic.…”
Section: Neuropilins and The Primary Ciliummentioning
confidence: 99%
“…Referring to the primary cilium, studies conducted by Pinskey et al [68] found that NRP1 and NRP2 promote the activation of Gli transcription factor. Interestingly, the authors found that a conserved 12 amino acid region of the NRP1 cytoplasmic domain between amino acids 890 and 902 is responsible for the HH-signal promotion.…”
Section: Neuropilins and The Primary Ciliummentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] The mechanisms for the role of NRP-1 in cancer progression rely on its interactions with several key signalling pathways in cancer cells, such as transforming growth factor β1 (TGFβ1), semaphorin (Sema), vascular endothelial growth factor (VEGF), hedgehog (HH), interferon-γ (IFNγ) and GAIP/RGS19-interacting protein (GIPC1). [15][16][17][18][19][20] Therefore, targeting NRP-1 has been shown to be a potential therapeutic target for some cancers. 21,22 However, the role of NRP-1 in GBC remains unclear.…”
Section: Introductionmentioning
confidence: 99%